2013
DOI: 10.11591/edulearn.v7i2.220
|View full text |Cite
|
Sign up to set email alerts
|

Barriers To Successful Implementation of STEM Education

Abstract: The implementation of STEM education in schools across the globe is to prepare the future workforce with strong scientific and mathematical backgrounds to enhance skills development across STEM disciplines. However, for STEM education to achieve its goals and objectives, addressing the barriers to STEM education should start by fixing the problems at the elementary, junior and senior high school levels; the grassroots and potential feeders to colleges and universities. Since many nations including the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(150 citation statements)
references
References 23 publications
3
108
0
21
Order By: Relevance
“…This can present a challenge for elementary teachers, who often have limited disciplinary knowledge within science, technology, engineering, and mathematics (Sanders 2008;Ejiwale 2013). However, Kelley and Knowles (2016) suggest that the key to preparing STEM educators is to first begin by grounding their conceptual understanding of integrated STEM education within key learning theories, and pedagogical approaches, and then building awareness of research results of current STEM educational initiatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can present a challenge for elementary teachers, who often have limited disciplinary knowledge within science, technology, engineering, and mathematics (Sanders 2008;Ejiwale 2013). However, Kelley and Knowles (2016) suggest that the key to preparing STEM educators is to first begin by grounding their conceptual understanding of integrated STEM education within key learning theories, and pedagogical approaches, and then building awareness of research results of current STEM educational initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that PD must be active, sustained, coherent, collaborative, reflective, and focus on content knowledge in order to lead to real changes in practice (Garet et al 2001;Gamoran et al 2006). Within STEM PD, research has found that there is a need to help teachers develop deeper understandings of disciplinary knowledge within the four disciplines (Brophy et al 2008;Cunningham and Hester 2007;Ejiwale 2013), explore various mechanisms for integrating content across the disciplines (Moore, Stolhmann et al 2014;Wang et al 2011), and develop beliefs and understandings related to integrated STEM education Stohlmann et al 2012). Despite the existence of several PD opportunities focused on integrating STEM at the elementary level, there is limited research examining specific content and skills that are preferred when teaching integrated STEM and how these content and skills can be imparted to help with the widespread adoption of integrated STEM in elementary classrooms (O'Brien et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing amount of evidence to support the notion that youth require a strong foundation in science, technology, engineering, and math (STEM) education in order to enhance economic well-being and quality of life during later years in life (Ejiwale, 2013;Let's Talk Science & Amgen Canada, 2014; President's Council of Advisors on Science and Technology, 2010). Across North America, the importance of STEM education at the post-secondary level has been emphasized as a significant portion of careers will require some form of STEM literacy and skills (Let's Talk Science & Amgen Canada, 2014;Mahy & Krimmel, 2008; President's Council of Advisors on Science and Technology, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Despite its practicality as a conceptual tool for organization of the chemical elements and understanding their properties, most teachers experience difficulties when teaching science content at secondary school level (Mokiwa 2014a;2014b;Mudau, 2013;Ejiwale, 2013;Jita & Ndlalane, 2009). The issues of what kind of knowledge is adequate for making effective instructional decisions or designing appropriate learning environments are on the agenda of current research world-wide (Malcolm & Alant, 2004).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…However, for many Physical Sciences teachers, this topic is considered difficult to teach where several studies reported that the majority of teachers experience difficulties when teaching science content at secondary school level (Mokiwa 2014a;2014b;Mudau, 2013;Ejiwale, 2013;Jita & Ndlalane, 2009). In the South African context, Physical Sciences is a subject that investigate physical and chemical phenomenon and it is taught from grades 9 to 12.…”
Section: Introductionmentioning
confidence: 99%